STATUS KEBERLANJUTAN KETERSEDIAAN SUMBERDAYA PERIKANAN CAKALANG (Katsuwonus pelamis) DI PERAIRAN ACEH BARAT - Edwarsyah Edwarsyah; Mohamad Gazali (Universitas Teuku Umar, 2015)
Fisheries production in West of Aceh was still insufficient to provide the local community consumption. However, fisheries resources in West of Aceh water are abundant. But utilization of fisheries particularly skipjack tuna (cakalang) hasn’t been yet optimalized. This aiming to analyse the status of sustainablity of skipjack (Katsuwonus pelamis) fisheries in West of Aceh water. The study was conducted in November to Desember 2012 at the Fish Landing Port of Kuala Bubon and Fish Landing Bases (PPI) Ujong Baroh. The result shown that sustainability index value by using multidimensional scaling is 88,42 with stress value is 0.12 and coefisien of determination (R2) is 0,95 or 95%. Such index value show that sustainablity of skipjack resources were good status. It means that multidimensional of skipjack stock were still paid attention in fisheries management sustainable. Beside that, it shown from water condition and fishing gears were still support viability of such comodity.